2022
DOI: 10.1002/14651858.cd001970.pub6
|View full text |Cite
|
Sign up to set email alerts
|

Delayed introduction of progressive enteral feeds to prevent necrotising enterocolitis in very low birth weight infants

Abstract: Delayed introduction of progressive enteral feeds to prevent necrotising enterocolitis in very low birth weight infants (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…Preterm infants diagnosed with NEC often have a variety of long-term complications, which have caused a huge economic burden to the family and society. Therefore, the prevention of NEC is more important than the treatment of NEC ( 15 ). Current studies mostly believe that OAC may prevent NEC through the following aspects: (1) enhance the interaction between cytokines in colostrum and oropharyngeal mucosal tissues to provide systemic protective immunostimulatory effects; (2) protective biokines exert their antibacterial, anti-inflammatory, immunomodulatory, and antioxidant effects; (3) establish mucosal barrier protection against pathogens; (4) oligosaccharides prevent pathogen colonization, proliferation, and translocation not only by promoting symbiotic bacterial colonization but also by direct interaction with epithelial cells to maintain intestinal integrity; (5) anti-inflammatory effects; and (6) antioxidant effects ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preterm infants diagnosed with NEC often have a variety of long-term complications, which have caused a huge economic burden to the family and society. Therefore, the prevention of NEC is more important than the treatment of NEC ( 15 ). Current studies mostly believe that OAC may prevent NEC through the following aspects: (1) enhance the interaction between cytokines in colostrum and oropharyngeal mucosal tissues to provide systemic protective immunostimulatory effects; (2) protective biokines exert their antibacterial, anti-inflammatory, immunomodulatory, and antioxidant effects; (3) establish mucosal barrier protection against pathogens; (4) oligosaccharides prevent pathogen colonization, proliferation, and translocation not only by promoting symbiotic bacterial colonization but also by direct interaction with epithelial cells to maintain intestinal integrity; (5) anti-inflammatory effects; and (6) antioxidant effects ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…As previously acknowledged, the research on the extremely preterm or ELBW population is less concrete compared to larger infants, such as those born VLBW (<1500 g) or even at low birth weights (<2500 g). This is likely due to the smaller number of ELBW infant births, the inclusion of growth-restricted infants who are ELBW but not extremely preterm, the general variability in acuity after birth, and the increased challenges of conducting clinical research [ 4 , 26 , 27 ]. While quandaries may also exist in older or larger populations, these are less helpful in a more extreme population and when results may not be fully extrapolated.…”
Section: Current Evidencementioning
confidence: 99%
“…The variability of the available literature is exemplified in regard to enteral feeding management. For instance, in VLBW infants (which also includes subsets of ELBW infants), a 2022 Cochrane review revealed that delaying the introduction of enteral feedings has no impact on the risk of developing necrotizing enterocolitis [ 27 ]. Likewise, the delayed introduction of enteral feedings results in intestinal villous atrophy [ 28 , 29 ] and prolongs the duration to achieve full enteral feeding [ 27 ].…”
Section: Current Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…3 Recent randomized clinical trials (RCTs) evaluating enteral feeding initiation and/or advancements have demonstrated benefits such as reduction in the use of parenteral nutrition, the need for central venous access, and the risk of invasive infections, all without any increase in risk of SIP or NEC. [4][5][6][7][8] Following the clear and significant benefits inferred from early use of human milk for VLBW infants, 9 the practice of providing trophic feeding has been largely accepted. However, practices regarding the ideal time for initiation of enteral feeding, the duration and volume of initial feedings, and the rate of progression of feeding volumes to establish full enteral feeding among VLBW infants are widely variable.…”
Section: Introductionmentioning
confidence: 99%